PENYUSUNAN PAKET WISATA BUDAYA DIKABUPATEN TANAH DATAR PROVINSI SUMATRA BARAT - Hanif, Muhammad; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to design a Cultural Tourism Package Arrangement in Tanah Datar District, West Sumatra Province. This study used a qualitative method with a qualitative descriptive approach to explain and describe the conditions that occurred at the research location by collecting data and information in the field. The informants in this study are the Head of Service, Tourism Managers, and the Community. In this study, the data collection techniques used were case studies, interviews, observation and documentation. Based on the results of the research, it can be concluded that cultural tourism in Tanah Datar is very abundant and diverse, so that with this abundance and variety, tourist visits should increase every year. Coupled with the sale of Cultural Tourism Packages in the future, it will make tourists more interested in visiting Tanah Datar Regency. In addition, this Cultural Tourism Package can provide additional information for tourists about what tours are in Tanah Datar Regency. Key words: Preparation.Cultural.Tour Packages. Tanah Datar District